DEVELOPMENT OF FOREIGN LANGUAGE COMMUNICATION SKILLS OF TECHNICAL UNIVERSITY STUDENTS IN THE PROCESS OF DISTANCE TEACHING (Proceedings of International Educators Conference, 2024)
The purpose of the study is to present a rationale for ways to develop foreign language communicative skills of technical university students in a distance learning environment. The article describes a complex of theoretical and methodological approaches that reveal the systemic, competence-based and activity-based foundations of the process being studied. Scientific novelty is determined by the fact that a system has been developed for developing communication skills of future engineers in a distance format, and a set of exercises has been proposed for organizing students’ work in foreign language classes. As a result of the experiment, positive dynamics were obtained in the levels of communication skills of students in the experimental group.